FACTORS OF COMMUNICATION STRATEGIES FOR HINDU RELIGIOUS EDUCATORS IN THE DIGITAL ERA - I Nyoman Surpa Adisatra; Bagus Ade Tegar Prabawa (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
The rapidly evolving digital communication in today's era has made digital-based communication strategies for religious educators increasingly crucial and relevant. With the changing behavioral patterns of a society that heavily relies on technology, especially digital platforms, in daily life, religious educators need to adapt their communication approaches to effectively reach their audience. The utilization of digital platforms, such as social media, websites, and specialized applications, presents new opportunities to convey religious messages, facilitate discussions, and build larger online communities. Therefore, the development of digital-based communication strategies for religious educators is not just a necessity but an imperative to respond to the dynamics of the times and strengthen the connection between religious messages and the continually evolving digital society. The sustainability of digital-based communication strategies for religious educators can also be measured through data analysis and feedback obtained from online interactions. Using the analytical tools available on digital platforms, religious educators can evaluate the extent to which religious messages are absorbed and understood by the audience. The aim of this research is to determine whether digital-based communication strategies for religious educators can effectively enhance understanding, engagement, and compliance with religious values and to identify factors that can influence the success of implementing digital-based communication strategies among religious educators. The data analysis technique used involves clarification, interpretation, and gradual conclusion drawing steps. The collected data is processed by selecting, analyzing, and then presented in article form. The results of this research indicate that fundamentally, Hindu religious educators have three functions: consultative and advocacy functions, informative function, and educational function. These are expected to contribute positively to the spiritual, moral, and social development of the Hindu community and strengthen religious values in daily life. Therefore, it is crucial for Hindu religious educators to understand digital-based communication strategies, which require not only technological understanding but also active community involvement, creativity in educational content, institutional support, cultural adaptation, continuous evaluation, and responsibility for change. This provides a holistic view of key factors that can influence the success of conducting religious communication through digital media.